PENDAMPING UMKM (PENGELOLAAN KEUANGAN DAN MANAJEMEN USAHA) SERTA PENGELOLAAN PRODUK AGRIBISNIS PERTANIAN BUAH NANAS DESA TANJUNG BARU - Nabillah, Bella (Transpublika Publisher, 2022)
Community service with the topic of financial management and business management is an activity that involves students and supervisors. The focus of this service is on a theme or activity. This community service activity helps provide training and processing of pineapple fruit products in order to improve the economy of the Tanjung Baru community. This qualitative research method is used in this project. The result of this series of non-profit activities is the development of pineapple processed products with more modern and online-based packaging and marketing such as Facebook, WhatsApp and Instagram. It is hoped that after completing this service program, individuals who take part in this training have broad knowledge and insight and dare to continue to innovate and improve creativity to improve their standard of living for the better.